Data based investigation of the peer education methods on self-efficacy in patients with myocardial infarction using a randomized control trial design - Mohammadpourhodki, Reza (Data Brief, 2018)
This database aims to show the effects of peer-education (PE) on self-efficacy in patients with MI referring to Zabol Emam Ali Hospital in 2016. The data provided in this paper are for a descriptive-analytical and experimental study which included 70 patients with MI that randomly assigned to PE group (n = 35) and control group (n = 35). We used two tools for data collection in this data article. Patient׳s demographic data questionnaire, consisting of two parts: the first section had questions about general details such as age, education, marital status, while the second section had questions about health status information. Cardiac self-efficacy questionnaire was the second questionnaire. Finally, the data of 30 intervention and 30 control individuals were then analyzed by SPSS software and P value < 0.05 was considered to be statistically significant. The data indicated that PE can be useful for providing a better care in MI patients, thus, it is recommended that it׳s better to use this training method besides the routine training of nurses for MI patients.